Emigration and tobacco smoking among those staying behind - Artjoms Ivlevs; Roswitha M. King (Journal of Migration and Health)
High or growing rates of smoking tobacco and high rates of emigration are salient features of many low- and middle-income countries, yet the links between migration and smoking remain underexplored. We study the effects of household member emigration on the likelihood of smoking among those staying behind in the countries of former Yugoslavia. Using instrumental variable analysis, we find that the emigration of household members reduces the likelihood of smoking, especially among women and older respondents. These findings support the ‘social remittances’ hypothesis that migration contributes to the transfer of smoking-related norms from destination to source countries. Migration may thus contribute to socioeconomic development of source countries by reducing one of the world's biggest health epidemics: smoking.